Rural areas as a territory for innovation - Zajda, Katarzyna (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2015)
Abstract: The process of innovation is territorially embedded. In literature on the subject, the town (especially metropolitan areas) is presented as the “natural” environment for innovation. However, although the resources of rural areas limit their potential for creating and implementing technological innovation, they still provide opportunities for creating and implementing social innovation. This article presents the assumptions of the proximity paradigm (l’ekonomie de proximité) and a regional innovation system theory which refer to defining the importance of territory in an innovation processes. The article discusses the determinants for creating local systems of social innovation in rural areas.Various dimensions of relationships between different entities (based n data contained in literature), i.e. between public institutions (including local authorities), non-governmental organizations (including local action groups) and enterprises (including social enterprises) were analyzed This analysis showed that the territories which manifest an ability to create local innovative systems and those with low potential, in this regard, can be identified.
Keywords: innovative territory; social innovations; proximity paradigm; regional innovation system theory; social innovation systems